PERANCANGAN CORPORATE IDENTITY PERPUSTAKAAN BANK INDONESIA SURABAYA SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Ratna, Anisa Ayu; Bahruddin, Muh; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2015)
Abstract: Perpustakaan Bank Indonesia SurabayaÂ is a growing library company in Surabaya. The problem is, a lot of competitors threaten the sales position of Perpustakaan Bank Indonesia Surabaya. During this, media campaign that used by Perpustakaan Bank Indonesia Surabaya does not have concept design. The low awareness of the importance the media campaign, create a high probability of customers moving to another library. Media campaigns are very important to build brand equity. Therefore, it is necessary to increase customer aware by doing branding and maintenance customers through the media campaign to maintain the position of Perpustakaan Bank Indonesia Surabaya from the competitors. The design is done by observation, interviews, depth interviews, and literature studies using qualitative-descriptive analysis and supported by existing analysis, SWOT and STP obtained brilliant concept that is used in overall design. The concept of brilliant implemented using product photo illustration of Perpustakaan Bank Indonesia Surabaya. Unique concept realized by unique form of media, while the brilliant concept realized from the arrangement of layout and color selection. The concept was subsequently applied in corporate identity and promotional media like Graphics Standart ManualÂ that can be able to increase customer awareness.Â Keywords: : Design, Corporate Identity, Perpustakaan Bank Indonesia Surabaya, Graphics Standart Manual, Brand Awareness, Brilliant